tim x biet
\(\frac{-5}{6}-x=\frac{7}{12}+\frac{-1}{3}\)
Tim x biet:
\(\frac{6}{x^2+2}+\frac{12}{x^2+8}=3-\frac{7}{x^2+3}\)
tim x biet
a\(\frac{3}{5}:\frac{7}{x}:\frac{3}{4}=\frac{8}{35}\)
b,\(x< \frac{7}{12}:\frac{4}{5}\)
Tim x biet
c) \(x-3\frac{1}{2}x=-2\frac{6}{7}\)
d) \(-2\frac{1}{3}x-1\frac{3}{4}x+3\frac{2}{3}=3\frac{3}{5}\)
Tim x biet
d) \(\frac{x-1}{21}=\frac{3}{x+1}\)
e) \(2\frac{7}{9}-\frac{12}{13}x=\frac{7}{9}\)
\(\frac{x-1}{21}=\frac{3}{x+1}\)
=> \(\left(x-1\right)\left(x+1\right)=21\cdot3\)
=> \(x^2-1=63\)
=> \(x^2=64\)
=> \(\orbr{\begin{cases}x^2=8^2\\x^2=\left(-8\right)^2\end{cases}\Rightarrow}\orbr{\begin{cases}x=8\\x=-8\end{cases}}\)
\(2\frac{7}{9}-\frac{12}{13}x=\frac{7}{9}\)
=> \(\frac{12}{13}x=2\)
=> \(x=\frac{13}{6}\)
d, \(\frac{x-1}{21}=\frac{3}{x+1}\)
\(\Leftrightarrow\left(x-1\right)\left(x+1\right)=63\)
\(\Leftrightarrow x^2-1=63\Leftrightarrow x^2=64\Leftrightarrow x=\pm8\)
e, \(2\frac{7}{9}-\frac{12}{13}x=\frac{7}{9}\)
\(\Leftrightarrow\frac{12}{13}x=2\Leftrightarrow x=\frac{13}{6}\)
Tim x biet
\(-5\left(x+\frac{1}{5}\right)-\frac{1}{2}\left(x-\frac{2}{3}\right)=\frac{3}{2}x-\frac{5}{6}\)
-5.(x+1/5) -1/2.(x-2/3)=3/2x-5/6
-5x + (-1) -1/2x -1/3=3/2x-5/6
-5x-1/2x-3/2x=1+1/3-5/6
x.(-5-1/2-3/2)= 6/6+2/6+(-5/6)
x.(-10/2+(-1/2)+(-3/2))=3/6
x.6/2=1/2
x=1/2:6/2
x=1/6
Vậy x = 1/6
Tim x biet
c) x - \(\frac{5}{7}=\frac{2}{7}.\frac{11}{5}\)
d)\(\frac{2x}{5}=\frac{6}{2x+1}\)
Tim x , biet
c) x - \(\frac{5}{7}=\frac{2}{7}.\frac{11}{5}\)
d) \(\frac{2x}{5}=\frac{6}{2x-1}\)
-1/5
nha
>: kệ đề bài nhá, bài cho j lm cái đó.
a, \(\frac{-5}{7}+\frac{3}{4}+\frac{-1}{5}+\frac{-2}{7}+\frac{1}{4}\)
\(\frac{-5}{7}+\frac{3}{4}-\frac{1}{5}-\frac{2}{7}+\frac{1}{4}=-1+1-\frac{1}{5}=-\frac{1}{5}\)
b, \(\frac{-3}{31}+\frac{-6}{17}+\frac{1}{25}+\frac{-28}{31}+\frac{-11}{17}+\frac{-1}{5}\)
\(=\frac{-3}{31}-\frac{6}{17}+\frac{1}{25}-\frac{28}{31}-\frac{11}{17}-\frac{1}{5}=-1-1-\frac{4}{25}==-2-\frac{4}{25}=-\frac{54}{25}\)
Sai j sửa hộ.
1) Tinh :a) \(\frac{3^6.45^4-15^{13}.5^{-9}}{27^4.25^3+45^6}-\frac{50}{7}.\frac{\sqrt{0,49}}{25}\)
b) Tim x , biet: \(|2x-\frac{1}{5}|\left(-\frac{1}{5}\right)^5=\left(-\frac{1}{5}\right)^7\)
Tim x biet
a)x - \(\frac{5}{7}=\frac{1}{9}\)
b) \(\frac{-3}{7}-x=\frac{4}{5}+\frac{-2}{3}\)